2020
DOI: 10.3390/su12197874
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Readiness for Emergencies and Public Health Challenges—The Case of Saudi Arabia

Abstract: This study was aimed at assessing the readiness of 200 emergency nurses in the southern part of Saudi Arabia in the management of public health emergencies, major incidents, and disasters by using quantitative research through a self-reporting validated questionnaire containing 10 different dimensions. All registered nurses working in emergency departments who were willing to participate, of all ages and gender groups, were included. Nurses who were not present during the study period because of vacation or ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
23
3
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 31 publications
1
23
3
1
Order By: Relevance
“…The participating nurses reported good perceived knowledge in almost all investigated aspects of the theoretical dimensions, but perceived weaknesses in practical dimensions of emergency management and difficulties in assessing their own efforts. Simulation exercises, including theoretical and practical aspects of emergency management, were suggested to continuously examine and strengthen nurses' knowledge, skills, and abilities [9]. These results are concordant with those reported by Diakakis et al, who also found a correlation between knowledge and perception of risks and readiness with personal characteristics of participants, such as education level, qualification, age, years in service, etc., whereas, handling the everyday issues, practices and processes was correlated with their positions in the hierarchical chain [10].…”
supporting
confidence: 84%
“…The participating nurses reported good perceived knowledge in almost all investigated aspects of the theoretical dimensions, but perceived weaknesses in practical dimensions of emergency management and difficulties in assessing their own efforts. Simulation exercises, including theoretical and practical aspects of emergency management, were suggested to continuously examine and strengthen nurses' knowledge, skills, and abilities [9]. These results are concordant with those reported by Diakakis et al, who also found a correlation between knowledge and perception of risks and readiness with personal characteristics of participants, such as education level, qualification, age, years in service, etc., whereas, handling the everyday issues, practices and processes was correlated with their positions in the hierarchical chain [10].…”
supporting
confidence: 84%
“…In this study, we examined healthcare workers’ perceptions of preparedness and willingness to work during disasters and emergencies in the southern region of the KSA. The primary reason for choosing this area for an evaluation was the continuous exposure of the region to both manmade and natural disasters, and earlier evaluation of their knowledge and competences [ 23 ]. The findings in this study indicate that although a high number of participants had training in disaster management, and were supposed to be prepared to respond to one, most of them were unwilling to provide care unconditionally except when dealing with natural disasters and a seasonal influenza pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of this group showed that the majority of emergency staff at hospitals in the southern region of the KSA had good theoretical knowledge but insufficient practical knowledge. The study also showed that staffs with greater educational knowledge were more confident to act in emergencies and disaster events [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…It verifies the effectiveness of completed training, the retention of knowledge and skills of healthcare workers, and can be used to determine perceptions of self-competence, reinforcing learning. Numerous studies suggested that health care workers, confident in their own high level of competence, are more likely to react effectively in real crisis situations and more often than workers who perceive their competence as being low [16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%